The Effect of Auditors’ Accountability, Independence, and Experience on Audit Service Quality (Survey on Public Accounting Firms in DKI Jakarta in 2022) - Hernawan, Rivatedi Rona; Setiyawati, Hari (Advances in Social Sciences Research Journal, 2022)
The public accounting profession has an important role in auditing financial statements in an organization and is a profession of public trust. Public accountants, tasked with assessing and verifying the financial statements issued by the company's management, and ultimately provide their opinion on the financial statements they have audited. This study examines the effect of accountability, independence, and auditors' experience on the quality of audit services and the impacts on clients' satisfaction at Public Accounting Firms in DKI Jakarta in 2022. The population of this study was 221 Public Accounting Firms in Jakarta, and the samples were 90 auditors. The data were obtained by using a questionnaire. This study used Structural Equation Modeling (SEM) as the data analysis with PLS as the test tool. The results showed that accountability, independence, and auditors' experience had a significant positive effect on audit quality.